(untitled) (Journal of the Bangladesh Agricultural University, 2020)
Poultry farm could be potential source for antibiotic resistant bacteria. Present study was designed to determine total load of viable bacteria, Escherichia coli, Salmonella spp. and Staphylococcus spp. in different components of poultry farm environments; followed by detection of their antibiogram. A total of 75 samples of six different types (poultry droppings-15, litter-15, poultry feed-15, bird handler’s hand wash-10, water-10, and air-10) were collected from five poultry farms. Bacterial total counts were done by spot diffusion method followed by isolation and identification of E. coli, Salmonella spp., and Staphylococcus spp. based on morphology, cultural, staining, and biochemical test. Antimicrobial resistant profiles were determined by disk diffusion method. The mean total bacterial count, E. coli, Salmonella spp., and Staphylococcus spp. count ranged from 3.44±0.65 to 9.22±0.55, 0±0 to 7.12±0.37, 0±0 to 5.84±0.20, and 0±0 to 8.45±.0.15 log CFU/gm or ml, respectively. Of 75 samples, 43 (57.33%), 33 (44%), and 38 (50.67%) samples were positive as E. coli, Salmonella spp., and Staphylococcus spp., respectively. Antibiogram study revealed 42.1% Staphylococcus spp. resistance to oxacillin i.e. MRSA in nature. Interestingly, E. coli and Salmonella showed 48.84% and 54.55% resistance to colistin. In addition, isolated bacteria also showed various degree of resistance against gentamicin, ciprofloxacin, ampicillin, oxytetracycline and chloramphenicol. Antibiotic resistant E. coli, Salmonella spp., and Staphylococcus spp. were detected from poultry farm environments that has the chance to enter into the food chain and poses serious threat to human health. J Bangladesh Agril Univ 18(3): 615–622, 2020 https://doi.org/10.5455/JBAU.98074